Real-Time Optimal Control Technique of A Rotary Inverted Pendulum System - M.A.H., M.Nazri; Mohd, Hafiz Jali; Hafez , Sarkawi (2013)
This paper presents a real time control technique to stabilize inverted pendulum in the vertical upright position. Stabilize the inverted pendulum is a classical control problem that could be related to some problems in industrial applications. Two common problems that always been encountered by inverted pendulum system is unstable behavior and nonlinear. This lead to numerous studies on the control algorithm to balance the inverted pendulum system in the vertical upright position. Generally, inverted pendulum is mounted on DC motor and is equipped with sensor to measure angular displacement. Inverted pendulum has the same analogy with human that try to balance a broomstick using fingertip. Balancing the Inverted Pendulum requires a good control system. Therefore an optimal control technique is proposed to achieve desired design requirement which are less than 5% overshoot and less than 5 seconds settling time. The controller is optimized to achieve the best performance result. Finally the performance of the controller is compared with PID controller as a benchmark.